ELEPHANT ME - Andreae, Giles; Parker-Rees, Guy (London : ORCHARD BOOKS, 2022)
The empowering story of little elephant Num-Num, who discovers the importance of simply being YOU! From the creators of international bestseller and much-loved classic Giraffes Can't Dance. Now in a sturdy board book format - perfect for the even the littlest hands. It's time for the Elephant Games! One by one, the young elephants compete to impress King Elephant Mighty and earn their Elephant Name. Nina is the strongest, so she becomes Elephant Strong. Norcus is the loudest, so he becomes Elephant Noisy. Little Elephant Num-Num thinks he will never discover his own special talent - until he learns that the very best thing you can be is YOU!
Keywords: Readers -- Fiction